2006
DOI: 10.1002/adma.200600714
|View full text |Cite
|
Sign up to set email alerts
|

The Microstructure of Biogenic Calcite: A View by High‐Resolution Synchrotron Powder Diffraction

Abstract: Biogenic crystals, i.e., crystals produced by living organisms, have attracted a great deal of attention in latter years because of their fascinating microstructures and superior properties. [1][2][3] The interrelation between the microstructure of materials and their properties is a key issue of materials science. Impressive examples of scientific achievements in this field include our ability to control the strength of metals and alloys by annealing-mediated grain size, [4] and bandgap engineering in semicon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
184
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 130 publications
(208 citation statements)
references
References 34 publications
23
184
1
Order By: Relevance
“…These findings allowed us to conclude that organic macromolecules facilitate the crystal growth in certain directions. Moreover, these molecules are apparently attached to appropriate atomic planes (and the (012)-plane has a favorable atomic structure described above) being in registry with some atomic groups of calcite (16). At this stage, we indicate deep involvement of the specific atomic plane in crystal growth and twinning, both in the presence of organic macromolecules, which may be important for further studies of biomineralization.…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…These findings allowed us to conclude that organic macromolecules facilitate the crystal growth in certain directions. Moreover, these molecules are apparently attached to appropriate atomic planes (and the (012)-plane has a favorable atomic structure described above) being in registry with some atomic groups of calcite (16). At this stage, we indicate deep involvement of the specific atomic plane in crystal growth and twinning, both in the presence of organic macromolecules, which may be important for further studies of biomineralization.…”
Section: Resultsmentioning
confidence: 85%
“…Note that, according to our recent structural study (16), the (012)-plane may play an important role in the growth of biogenic calcite. In particular, we observed that crystallite sizes in calcitic shell P. nobilis, from which the specific protein Caspartin was extracted, are highly anisotropic, reaching the maximum (Ϸ800 nm) along the normal to the (012)-plane.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 25,32 ] Nevertheless, comparison of the calcite prisms from a range of mollusks has revealed species-specifi c variations in the microstrain and macrostrain, [ 25,33 ] where these have been attributed to differences in the compositions of the macromolecules, rather than the amounts occluded. [ 34 ] Investigations have therefore often focused on calcite crystals coprecipitated with extracted molecules, where XRD spectra from calcite crystals occluding the small protein perlucin [ 24 ] showed smaller peak shifts than calcite precipitated in the presence of "caspartin," a 17 kDa protein extracted from the calcitic prisms of Pinna nobilis .…”
Section: Discussionmentioning
confidence: 99%
“…Peak broadening is commonly reported on heating both synthetic and biogenic calcite crystals containing occluded organic phases, where this is attributed to the creation of new interfaces. [ 9,24,25 ] The vesicle/calcite crystals were therefore subjected to isochronous annealing for 30 min at intervals of 100 °C from 100-600 °C and patterns were recorded after the samples had cooled to room temperature after each heating cycle. Peak shifts to smaller d -values began on heating to 300 °C, where this continues on heating to higher temperatures ( Figure 5 a,b).…”
Section: Microstructures Of the Nanocomposite Crystalsmentioning
confidence: 99%